(untitled) (Journal of the College of Basic Education, 2022)
The Arabic language is the best language in the world because it was chosen as the last language of a divine message, as it is a tool of understanding between Arabs and Muslims, as it remains and timeless with the eternity of the Holy Qur’an. Arabic was and still is the best tool for expression. For all branches of the Arabic language because one pours into it the most valuable thoughts and feelings he has, so it is his right on us in the field of education that we pay the utmost care and attention to methods of teaching it. However, weakness is prevalent in the share of expression and lack of interest in it, which is a prevalent problem in our schools. From this standpoint, recent trends emphasize helping learners with the harvest strategy in written expression. The researcher rewarded students statistically with the chronological age, sixth grade of primary school and the academic achievement of the parents. There were no statistically significant differences between the two research groups. The researcher prepared six serial posttests, a tool for her research, and relied on al-Rubaie correction tests with the two groups. Upon collecting data and analyzing it statistically, the study concluded the following: The experimental group students outperformed the control group and in light of the results some conclusions were drawn, from which the harvest strategy is considered one of the modern approaches to education, as its procedures have proven effective in teaching, and the harvest strategy helps the effective participation of students as well as addressing weaknesses in the students ’answers as it helps them On health thinking and expanding their linguistic wealth .The researcher suggested to continue her study:1- Adopting all kinds of harvesting strategies in the primary and preparatory curricula and colleges of education.2- Adopting the harvest strategy in teaching other branches of the Arabic language.